Management of Sustainable Consumption of Energy Resources in the Conditions of Digital Transformation of the Industrial Complex - Shinkevich, Marina V.; Mashkin, Nikolay A.; Ishmuradova, Izida I.; Kolosova, Valeria V.; Popova, Olga V. (International Journal of Energy Economics and Policy, 2020)
The purpose of the article is to study the dynamics of volumes and stability of the structure of energy resource consumption at manufacturing enterprises, the analysis of the technical readiness of energy systems to implement the ideas of digital transformation. As the main research methods used in this article there are the method of dipole energy analysis to determine the priority of types of energy carriers, the method of graphical visualization of data to find the release points of values from the zone of relative stability, the method of classifying objects to assign products to a group of objects on the level of energy sustainability. The article analyzes the current trends in energy consumption with the determination of the vector of sustainable energy consumption and the parameters of reserves for improving energy efficiency; prioritized separate types of energy production of petrochemical plants; the types of products were classified according to the level of sustainability of energy consumption with the establishment of control points having emissions of values from the zone of relative stability and unproductive consumption of energy resources; the high technical readiness of energy systems of manufacturing industries to automate production processes with the subsequent development of digital technologies has been proved. Keywords: energy efficiency, sustainable energy consumption, automated metering of energy resources, energy resources, dipole energy analysis. JEL Classifications: Ðž14, D24, Ð¡41 DOI: https://doi.org/10.32479/ijeep.10202